Morphological characterization and germination of Syagrus schizophylla (Mart.) Glass. (ARECACEAE) - Beltrame, Rômulo André; Jasmim, Janie Mendes; Vieira, Henrique Duarte (Comunicata Scientiae, 2019)
The interest in Syagrus schizophylla as an ornamental palm tree and the demand for conservation and preservation of the species led to this research. The objective was to study the physiological characteristics of its germination at different temperatures, as well as the morphological and biometrical characterization of diaspores and seedlings at the initial stages of growth and development. The research was divided into two experiments. In the first one, the aim was to identify the water absorption phases of seeds during germination under five scarification treatments as follows: intact diaspores, scarified diaspores, diaspores with endocarp rupture and intact seeds. In the second experiment, germination was tested at 25, 30 e 25 - 35 ºC; the first germination count, seedling emergence, abnormal seedlings, non-germinated seeds, the emergence curve, the emergence speed index and the mean time of emergence were evaluated. Afterwards, the morphological and biometrical characteristics of diaspores and seedlings were described. The water absorption curve observed under the different scarification treatments showed different water absorption patterns. Emergence percentages were 53, 61 and 47% at 25, 30 and 25 - 35 ºC, respectively. The highest emergence speed index was obtained at 30 ºC. The mean time of emergence was 30 days, approximately, under all the temperatures tested. The diaspores showed a great variability in both shape and size, presenting a globular to ovoid shape with an average length of 2.44 cm and an average width of 1.39 cm. The germination can be classified as hypogeal crypto cotyledonal of the remote-tubular type.